2013
DOI: 10.1007/s10396-013-0471-2
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration time ratio for the assessment of extracranial internal carotid artery stenosis

Abstract: Our results indicate that applying the AcT ratio can help in the diagnosis of ICA stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Although these past reports suggested that AcT and the AcT ratio were useful in the diagnosis of stenosis of ICA origin, there was still a variance with the ICA-AcT cutoff values of 85-150 ms [4,6,8], and AcT ratios of 1.31-1.75 [4,5,8], even in stenosis rates considered to be DSA-NAS-CET ≥ 50%.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Although these past reports suggested that AcT and the AcT ratio were useful in the diagnosis of stenosis of ICA origin, there was still a variance with the ICA-AcT cutoff values of 85-150 ms [4,6,8], and AcT ratios of 1.31-1.75 [4,5,8], even in stenosis rates considered to be DSA-NAS-CET ≥ 50%.…”
Section: Discussionmentioning
confidence: 89%
“…There are few reports on the diagnosis of ICA origin stenosis, where the AcT or the AcT ratio was used [4][5][6][7][8]. Takekawa et al [4] reported on 127 blood vessels, where the PSV and the ICA-AcT exhibited a significant positive correlation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations